Muslim calendar application: design specifications for elderly / Nur Farhana Abdullah - Abdullah, Nur Farhana (2013)
Calendar plays an important role as most people would refer to calendar to see and check the current and upcoming dates. As for Muslims, Muslims usually refer to Islamic calendar to know the dates in Islamic months. Moreover, Muslim elderly usually are the one cared to perform the obligatory and voluntary fasting. However, Islamic mobile calendar application for elderly is still limited. Many design guidelines can be found nowadays. Same goes to design guidelines for elderly. In contrast, design guidelines for elderly and younger generations differ a lot. This is due to elderly that encounter few limitations. In this study, there are five participants involved. Design guidelines were produced by the interview session answers from the participants. Improvements and enhancement on the Muslim Calendar Application interface design have been made by the feedbacks given by the participants. Also, adding a button in the design is considered necessary in order to design for mobile. However, only one button included to prevent confusion among elderly users. All in all, this study has achieved its objectives and delivered the outcome as expected.